THE ROLE OF THE HISTORY DISCIPLINE IN THE EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Tursunov X. (Modern American Journals, 2025)
This article analyzes the place and significance of the history discipline in Uzbekistan’s education system. History plays a vital role in fostering patriotism, shaping national consciousness, and studying cultural heritage among the younger generation. Within the framework of state education policy, the study examines the teaching of history and its legal-regulatory foundations. The paper also considers the role of modern teaching methods and innovative approaches in history education.
Keywords: Independence, education, history, law, Institute of History, university, higher education, concept, modern history of Uzbekistan.